Exploring the Entrepreneurial Spirit: Student Perspectives on Innovation, Education, And Career Aspirations - Sugeng Pradikto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The landscape of entrepreneurship education in Indonesia is undergoing a significant transformation, as exemplified by Universitas PGRI Wiranegara’s effort to instill entrepreneurial competencies in its students. This shift reflects a broader trend within the nation’s higher education system, emphasizing the development of an entrepreneurial mindset through various programs and initiatives.  The University, which evolved from STKIP PGRI Pasuruan in February 2020, likely employs mentorship programs, among other methods, to enhance student engagement and independence in entrepreneurship education. This article contrasts the current state of students’ entrepreneurial spirit with the aspirational goals, highlighting the gap between present conditions and ideal aspirations in students’ entrepreneurial journeys. It suggests that universities can bridge this gap by providing experiential learning opportunities, integrating entrepreneurship courses across disciplines, and fostering a culture of innovation and risk-taking. These strategies can create a supportive ecosystem for student entrepreneurs, preparing them for the challenges of the business world. Moreover, the research indicates that extracurricular activities have a more substantial impact on developing an entrepreneurial mindset than curricular activities. This finding underscores the importance of practical, real-world experiences in shaping entrepreneurial attitudes and skills